Food - Chrisp, Peter (Hove Wayland Publishers, 1994)
Looks at the diets and eating habits of both the rich and poor during the Tudor and Stuart period. Suggested level: primary, intermediate.
Include Color Illustration and Index
Keywords: Great Britain